PELABELAN TOTAL SISI TAK BERATURAN - (NIM : 20199005), Asmiati
Abstract : Let G = (V, E) be a graph with V(G) is its vertex set and E(G) is its edge set. Find the minimum value of k so that all vertices and edges can be labelled by 1, 2, ..., k (labels can be repeated), and having the property that all the weights of edges on G are different. The value of k is called the edge total irregularity strength of graph G, by notation tes(G). In this thesis, we shall show the general properties of the edge total irregularity strength of a graph. In particular, we find the strength for the following graphs: paths, book graphs, stars, complete bipartit and the disjoint union of some graphs.